Description and revalidation of Mansonia (Mansonia) fonsecai (Pinto) (Diptera: Culicidae) - Barbosa, Andreia Aparecida; Da Silva, Mário Antônio Navarro; Sallum, Maria Anice Mureb (Zootaxa, 2005)
Mansonia (Mansonia) fonsecai (Pinto 1932) is considered a valid species distinct from Mansonia indubitans Dyar & Shannon 1925. Morphological characters to distinguish Ma. fonsecai from Ma. indubitans are included. The adult female, male, genitalia, pupa, and fourth-instar larva of Ma. fonsecai are described and illustrated.